Tax planning and compliance for tax-exempt organizations rules, checklists, procedures 2024 cumulative supplement - Blazek, Jody (Wiley, 2024)
"This book is an indispensable guide to navigating the complex maze of nonprofit tax rules and regulations. A clear and fully cited description of the requirements for the various categories of tax-exempt entities from public charities, private foundations, civic associations, business leagues, and social clubs to title-holding companies and governmental entities can be found. Practical guidance on potential for income tax on revenue-producing enterprises along with explanations of many exceptions to taxability is provided. Issues raised by Internet activity, advertising, publishing, providing services, and much more are explained. This useful annual supplement for 2024 will cover any and all changes and updates to the law within the previous 12 month period and will keep accountants, attorneys, and others up-to-date for the year ahead"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Nonprofit organizations -- Taxation -- Law and legislation -- United States; Tax planning -- United States; Tax exemption -- United States; Planification fiscale; États-Unis; Impôt; Exemptions; États-Unis